2009
DOI: 10.1159/000231993
|View full text |Cite
|
Sign up to set email alerts
|

Cetrorelix, a Gonadotropin-Releasing Hormone Antagonist, Induces the Expression of Melatonin Receptor 1a in the Gonadotropin-Releasing Hormone Neuronal Cell Line GT1–7

Abstract: Melatonin has been implicated in the control of the reproductive system, and the modulatory actions of melatonin on gonadotropin-releasing hormone (GnRH) neurons have been assumed to be indirectly mediated through afferent neurons. However, our previous studies demonstrate sexually dimorphic modulation of A-type γ-aminobutyric acid (GABA) receptor (GABAAR) currents by melatonin in adult rat GnRH neurons and a preferential expression of melatonin 1a receptor (MT1) in male GnRH neurons. Using immortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
3
1
Order By: Relevance
“…However, despite this physiological effect, there was surprisingly no change in pituitary Mt1 expression. This finding contrasts with the ability of cetrorelix to induce MT1 receptor expression in the GT1-7 neuronal cell line [29] and suggests that changes during normal gonadotroph development maintain inhibition of Mt1 mRNA, despite the lack of GnRH signalling.…”
Section: Discussioncontrasting
confidence: 61%
“…However, despite this physiological effect, there was surprisingly no change in pituitary Mt1 expression. This finding contrasts with the ability of cetrorelix to induce MT1 receptor expression in the GT1-7 neuronal cell line [29] and suggests that changes during normal gonadotroph development maintain inhibition of Mt1 mRNA, despite the lack of GnRH signalling.…”
Section: Discussioncontrasting
confidence: 61%
“…Data represent mean ± SEM hypothalamic magnocellular peptidergic neurons [31]. In fact, we have recently shown that ambient GnRH downregulates the expression of melatonin receptors in GT1-7 cells [32].…”
Section: Discussionmentioning
confidence: 97%
“…Experimental studies [32,33] have shown that an increase in testicular androgen production occurs and peaks in the late gestational period, around E18 and continues in the first days of life [34]. Much of this testosterone is aromatized into estradiol and leads to the development of sexually dimorphic areas of the brain.…”
Section: Discussionmentioning
confidence: 99%